1997
DOI: 10.1074/jbc.272.15.10160
|View full text |Cite
|
Sign up to set email alerts
|

The Pax-5 Gene Is Alternatively Spliced during B-cell Development

Abstract: The transcription factor Pax-5 is expressed during the early stages of B-cell differentiation and influences the expression of several B-cell-specific genes. In addition to the existing isoform (Pax-5, which we have named Pax5a), we have isolated three new isoforms, Pax-5b, Pax5d, and Pax-5e, from murine spleen and B-lymphoid cell lines using library screenings and polymerase chain reaction amplification. Isoforms Pax-5b and Pax-5e have spliced out their second exon, resulting in proteins with only a partial D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 28 publications
(31 reference statements)
5
114
1
Order By: Relevance
“…1) was generously provided by Stephen Desiderio, Johns Hopkins University, Baltimore, MD (27) (29). Neither the N-terminal paired domain (DNA binding) nor the central domain of BSAP showed autonomous transcriptional activation, and hence both were candidates for detection of protein interactions in the two-hybrid transcriptional activation assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) was generously provided by Stephen Desiderio, Johns Hopkins University, Baltimore, MD (27) (29). Neither the N-terminal paired domain (DNA binding) nor the central domain of BSAP showed autonomous transcriptional activation, and hence both were candidates for detection of protein interactions in the two-hybrid transcriptional activation assay.…”
Section: Methodsmentioning
confidence: 99%
“…LexA-BSAP Constructs-LexA-BSAP fusion constructs for use in the two-hybrid assay were prepared by cloning PCR fragments amplified from pBSK-BSAP (27) into the EcoRI/SalI sites (underlined) of the pEG202 vector. All constructs were verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The blk promoter contains a previously uncharacterized NERF/ELF-1-binding site adjacent to a BSAP and AML1 site. Not much is known about regulation of blk gene expression, except that the B cell-specific transcription factor BSAP plays an important role and that the transcription factor NF-B/p50 interacts with the blk gene during B cell activation (41). We furthermore demonstrated that AML1 binds to the blk promoter and cooperatively transactivates the blk promoter in the presence of BSAP (43).…”
mentioning
confidence: 99%
“…Hematopoietic genes containing high affinity NERF/ ELF-1-binding sites include, among others, IgH and terminal deoxynucleotidyltransferase (34,35), mb-1 (membrane-bound immunoglobulin IgM-␣) and B29 (36), BSAP (37), lck (38), blk (B lymphoid kinase) (39), and lyn (40,41). Blk is a B cellspecific tyrosine kinase that is expressed in pre-B and mature B cells, but not in plasma cells; this is similar to the expression of mb-1 (membrane-bound immunoglobulin IgM-␣) and B29 (42).…”
mentioning
confidence: 99%
“…In addition to the paired box domain, PAX5 contains a partial onehelixed homeodomain and an 8-amino-acid octapeptide motif that functions as a transcriptional inhibitory motif (4). A number of alternatively spliced mRNA transcript variants have been described for both human and mouse PAX5, which result in both NH 2 -terminal and COOHterminal protein variations (10,11). Two developmentally regulated alternative PAX5 splice variants containing distinct 5′-exons (exon 1A and 1B), which encode two isoforms of PAX5 (PAX5α and PAX5β), were originally described by Busslinger et al (11).…”
Section: Introductionmentioning
confidence: 99%